An altered Physiological state of pseudomonas aeruginosa in the Biofilm Environment : effect on the algD promoter and a new attachment-inducible regulatory element - Brözel, Volker Siegfried (University of Pretoria, 2013)
Dissertation (MSc(Microbiology))--University of Pretoria, 2005.